PERANCANGAN STANDARD OPERATING PROCEDURE (SOP) REKRUTMEN DAN SELEKSI KARYAWAN DI PT X - Jane Margaretha; Tamara Cung Karisma; Daniel Lie (PROSIDING SERINA, 2021)
Organisations need to hire the most reliable employees in their fields for the sustainability of an organisation. However, some organisations face some human resources problems. For instance, most employees of PT X do not possess the appropriate competencies that are required for the completion of the tasks. This problem is caused by the current recruitment and selection process that is based entirely on interview in which prospective employees are asked only their personal life matters. This means that the interview method fails to assess the competencies for future employees. Furthermore, there is no other methods in determining their potentials too. The recommended intervention is to suggest a proper recruitment and selection system. In order for this process run consistently and not to miss any stage during the implementation, this recruitment and selection process is outlined in the form of a standard operating procedure (SOP). The information that needed for making the SOP was obtained by conducting interviews with the management and carrying out a scientific literature review. The completed SOP was then evaluated using the interview technique. According to the management, the SOP can aid the company to (a) select the most suitable employee to be placed in the designated position, (b) implement a more systematic and appropriate recruitment and selection system, and (c) improve its performance because the company could hire the most qualified employees. Moreover, PT X is advised to review the SOP periodically in order to have the most updated information and this SOP is recommended to be placed in the company’s master file so that they are well documented.